Characteristics of the Philosophical Approach in Education for the Teacher and the Leaner/ Khasâis al-Manhaj al-Falsafiy fi at-Tarbiyah wa at-Ta’lîm li al-Mua’allim wa al-Muta’allim - Huda, Ahmad Nawirul; Aini, Nur (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The curriculum has a position as the heart of educational activities, which will guide and pump all educational activities towards achieving educational goals. Philosophy is also called the